Inhibition of bone erosion, determined by high-resolution peripheral quantitative computed tomography (HR-pQCT), in rheumatoid arthritis patients receiving a conventional synthetic disease-modifying anti-rheumatic drug (csDMARD) plus denosumab vs csDMARD therapy alone: an open-label, randomized, parallel-group study - Naoki Iwamoto; Ko Chiba; Shuntaro Sato; Kazuteru Shiraishi; Kounosuke Watanabe; Nozomi Oki; Akitomo Okada; Tomohiro Koga; Shin-ya Kawashiri; Mami Tamai; Naoki Hosogaya; Masako Furuyama; et al. (Arthritis Research & Therapy, 2022)
Abstract Background This exploratory study compared the inhibition of bone erosion progression in rheumatoid arthritis (RA) patients treated with a conventional synthetic disease-modifying anti-rheumatic drug (csDMARD) plus denosumab versus csDMARD therapy alone and investigated the effects of denosumab on bone micro-architecture and other bone-related parameters using high-resolution peripheral quantitative computed tomography (HR-pQCT). Methods In this open-label, randomized, parallel-group study, patients with RA undergoing treatment with a csDMARD were randomly assigned (1:1) to continue csDMARD therapy alone or to continue csDMARDs with denosumab (60-mg subcutaneous injection once every 6 months) for 12 months. The primary endpoint was the change from baseline in the depth of bone erosion, measured by HR-pQCT, in the second and third metacarpal heads at 6 months after starting treatment. Exploratory endpoints were also evaluated, and adverse events (AEs) were monitored for safety. Results In total, 46 patients were enrolled, and 43 were included in the full analysis set (csDMARDs plus denosumab, N = 21; csDMARD therapy alone, N = 22). Most patients were female (88.4%), and the mean age was 65.3 years. The adjusted mean (95% confidence interval) change from baseline in the depth of bone erosion, measured by HR-pQCT, in the 2–3 metacarpal heads at 6 months was − 0.57 mm (− 1.52, 0.39 mm) in the csDMARDs plus denosumab group vs − 0.22 mm (− 0.97, 0.53 mm) in the csDMARD therapy alone group (between-group difference: − 0.35 mm [− 1.00, 0.31]; P = 0.2716). Similar results were shown for the adjusted mean between-group difference in the width and volume of bone erosion of the 2–3 metacarpal heads. Significant improvements in bone micro-architecture parameters were shown. The incidence of AEs and serious AEs was similar between the csDMARDs plus denosumab and the csDMARD therapy alone groups (AEs: 52.2% vs 56.5%; serious AEs: 4.3% vs 8.7%). Conclusions Although the addition of denosumab to csDMARDs did not find statistically significant improvements in bone erosion after 6 months of treatment, numerical improvements in these parameters suggest that the addition of denosumab to csDMARDs may be effective in inhibiting the progression of bone erosion and improving bone micro-architecture. Trial registration University Hospital Medical Information Network Clinical Trials Registry, UMIN000030575. Japan Registry for Clinical Trials, jRCTs071180018